Standardization of seed germination technique in Khurasani-ajavayan (Hyoscyamus niger) seeds - VERMA, SHER SINGH; VERMA, P K; VERMA, URMIL (The Indian Journal of Agricultural Sciences, 2014)
The Khurasani-ajvayan (Hyoscyamus niger L) is an important medicinal plant which is having high medicinal value. The germination test was conducted in the laboratory at three different temperatures (20, 25 and 30°C) and substrata (BP, TP and S). The results revealed that species having high percentage of hard seeds ranged from 58.0 -74.0% at 20°C followed by 25°C and 30°C which ranged from 42.0- 55.0% and 44.0 to 47.0%, respectively in all the substrata after 15 days of planting. To overcome this problem of low germination, the seeds were further subjected to various treatments, viz. seed soaking in water (24 and 48 hr), GA3 (200 and 500ppm), KNO3 (0.2%) and conc. sulphuric acid (H2SO4) 15 seconds to enhance seed germination and tested for seed germination after seed treatment. Among these treatments, GA3 (200 ppm) recorded the maximum normal seedlings (73.0%) in BP substrata followed by TP (68.0%) at 30°C after 12 days. Hard seeds were also reduced after soaking the seeds in water for 48 hr but it resulted in a subsequent increase in the dead seeds. KNO3 (0.2%) and GA3 (500 ppm) seed treatments enhanced the germination up to 50% as compared to control after 13 and 14 days, respectively irrespective of substrata and temperatures. Therefore, it is suggested that the seeds of Khurasani-ajvayan should be tested for germination in BP/TP substrata at 30°C after soaking the seeds in GA3 (200 ppm) solution for 24hours. The final count for germination should be taken after 12 days.